IMPLIKASI PENGATURAN PENYELESAIAN SENGKETA PERBANKAN SYARIAH MELALUI UNDANG-UNDANG NOMOR 21 TAHUN 2008-TERHADAP KEDUDUKAN HUKUM NASABAH - Anshori, Abdul Ghofur ([Yogyakarta] : Lembaga Penelitian dan Pengabdian Kepada Masyaraka, 2009)
The aim from this research to know the historical background from article 55 Act Number 2112008 about Shari a Banking; How the dispute resolution, which suitable with shari a principle; and the implication from this artide for customer legal standing. Implication related with legal protection for the customer as a party in financing agreement. Research about "The Implication of Dispute Resolution Regulation in Sharia Banking By Act Number 2112008 for The Customer Legal Standing" induded nonnative legal research, Le reseClrch based on library research to gain secondary data in law field. To complete data from library, so followed by field research. This research was held in Jakarta, i.e PT. Bank Muamalat Indonesia, PT. Bank Syariah Mandiri, PT Bank Syariah BRI, Bank Indonesia, Dewan Perwakilan Rakyat Republik Indonesia, Mahkamah Agung Republik Indonesia, and Badan Arbitrase Syariah Nasional. According to these research show that the historical background from artide 55 to give chance the parties use more variatif dispute resolution mechanism, to strenghten the freedom of contract principle. The resolution must be based on aI-au ran, Hadith, Fatwa DSN-MUI, and Regulation in Sharia Banking. By these way the implication from this make the customer legal standing stronger.